Розробка компонентів замовлення розробки та використання програмного забезпечення інформаційної системи біржі спостережень - Путілов, С. Ю. (ХНУРЕ, 2024)
The Publish-Subscribe pattern is an important pattern of behavior that helps automate the transmission of messages to the information system for further publication. Posted messages are categorized and sent to observers by the data administrator, giving them the ability to subscribe to specific tasks. This approach to the organization of information exchange allows you to effectively manage the flow of data and provides flexibility in responding to changes, which makes it extremely useful in the development of information systems. The choice of this design pattern is a strategic section, in addition, it contributes to increasing the speed, scalability and overall efficiency of information systems, making them more convenient and adapted to the needs of users.
Keywords: біржа спостережень